Intractable diarrhoea associated with secondary amyloidosis in rheumatoid arthritis. Issue 9 (1st September 1997) - Okuda, Yasuaki; Takasugi, Kiyoshi; Oyama, Tetsu; Oyama, Hiroko; Nanba, Shigeru; Miyamoto, Takeshi
Abstract : OBJECTIVE: To examine the clinical characteristics of intractable diarrhoea associated with secondary amyloidosis in rheumatoid arthritis (RA). METHODS: Of 179 RA patients with biopsy confirmed secondary amyloidosis, 24 cases (23 women and one man) with intractable diarrhoea lasting for more than one month were retrospectively evaluated. RESULTS: The mean (SD) duration of diarrhoea was 87 (64) days. Prodromal symptoms of gastrointestinal dysfunction (n = 21) and impaired peristalsis (n = 16) were observed. Laboratory data showed hypoproteinaemia (4.7 (0.85) g/dl) caused by malabsorption or protein loss and high values of C reactive protein (17.0 (9.3) mg/dl). Recurrence of intractable diarrhoea (n = 4) and transition from intractable diarrhoea to other gastrointestinal problems of amyloidosis (ischaemic colitis (n = 2) and intestinal pseudo-obstruction (n = 4)) were observed. In 19 patients (25 episodes) the duration of intravenous hyperalimentation at remission (18 episodes) was 68 (52) days. Corticosteroid pulse therapy was administered to 10 patients (11 times) and the time elapsed from the end of corticosteroid pulse therapy to the end of diarrhoea was 18 (14) days. One and five year survival rates after the onset of intractable diarrhoea were 73.4% and 38.9% . Seven of 13 patients (54%) had died as a result of infectious diseases. CONCLUSION: Intractable diarrhoea associated with secondary amyloidosis in RA is a serious clinical entity and the prognosis is poor. Although it is assumed that intravenous hyperalimentation treatment and corticosteroid pulse therapy are favourable regimens for intractable diarrhoea, the patients should be monitored for possible infectious complications.